Home environment of 11-year-old children born to parents with schizophrenia or bipolar disorder – a controlled, 4-year follow-up study: The Danish High Risk and Resilience Study – VIA 11. Issue 6 (25th April 2023) - Krantz, Mette Falkenberg; Hjorthøj, Carsten; Brandt, Julie Marie; Prøsch, Åsa Kremer; Rohd, Sinnika Birkehøj; Wilms, Martin; Veddum, Lotte; Steffensen, Nanna Lawaetz; Knudsen, Christina Bruun; Andreasen, Anna Krogh; Stadsgaard, Henriette; Hemager, Nicoline; et al.
Abstract: Background: The home environment has a major impact on child development. Parental severe mental illness can pose a challenge to the home environment of a child. We aimed to examine the home environment of children of parents with schizophrenia or bipolar disorder and controls longitudinally through at-home assessments. Methods: Assessments were conducted within The Danish High Risk and Resilience Study, a nationwide multi-center cohort study of children of parents with schizophrenia or bipolar disorder and population-based controls. The level of at-home stimulation and support was measured at age 7 ( N = 508 children) and age 11 ( N = 430 children) with the semi-structured HOME Inventory. Results from the 11-year follow-up study were analyzed and compared with 7-year baseline results to examine change across groups. Results: At age 11, children of parents with schizophrenia and bipolar disorder had lower levels of stimulation and support than controls (mean (s.d. ) = 46.16 (5.56), 46.87 (5.34) and 49.25 (4.37) respectively, p < 0.001). A higher proportion of children with parental schizophrenia or bipolar disorder lived in inadequate home environments at age 11, compared with controls ( N (%) = 24 (15.0), 12 (12.2) and 6 (3.5) respectively, p < 0.003). The changes in home environment scores did not differ across groups from age 7 to age 11. Conclusions: Assessed longitudinally from the children's age of 7 to 11, children of parents with schizophrenia or bipolar disorder had lower levels of stimulation and support in their homes than controls. Integrated support which can target practical, economic, social and health issues to improve the home environment is indicated.